Long-term outcomes in health-related quality of life influence chronic disease management in patients with pulmonary hypertension - Li, Jin-Ling; Xiao, Fan; Liu, Hong-Ting; Li, Hui-Ting; Zhao, Qin-Hua; Sun, Chun-Yan; Zhu, Yan; Yan, Lei; Wang, Wen-Yue; Luo, Hui; Gong, Su-Gang; Jiang, Rong; et al. (Frontiers in Cardiovascular Medicine, 2022)
Background Significantly improved survival in patients with pulmonary hypertension (PH) has raised interest in maintaining a good quality of long-term survivorship. In this study, health-related quality of life (HRQOL) measurement was used to assess the long-term changes of physical and mental outcomes. Methods A total of 559 consecutive inpatients with PH completed generic HRQOL (Short Form-36) who were diagnosed with PH by right heart catheterization. Assessments were carried out at short-term (1 year), midterm (3 years), and long-term (5 years) follow-ups. Results Patients with PH suffered more severe impairments in both physical and emotional domains than the U.S. population normative values. Patients with PH due to chronic lung disease had the worst physical component summary (PCS) score, but there was no difference in mental component summary (MCS) score among different PH types. A reduced PCS score was correlated with WHO FC severity and pulmonary vascular resistance (PVR). The Z score showed that the changing trend of mental conditions continuously declined from baseline to midterm and long-term follow-ups, but the PCS score seemed to be stable or improved. Cox regression analysis indicated increased baseline PVR and WHO FC III and IV, and decreased physical subscale of role physical, mental subscale of social functioning, and the MCS score have increased risk of mortality in the long-term follow-up. Conclusion Patients with PH have poor HRQOL. The long-term change of physical status seemed to be stable, but the mental state was continuously worse. These suggested identifying and intervening mental health progresses is a noteworthy issue in PH chronic management.